1991
DOI: 10.1366/0003702914335148
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Packaged Consumer Goods by Using FT-Raman Spectrometry

Abstract: The feasibility of obtaining FT-Raman spectra of consumer products inside clear polymeric packaging is described. It is possible to obtain high-quality spectra of the sample without removing it from the package, thus enabling quality-control checks to be performed on a final product. Examples are shown for three pharmaceutical preparations and one food product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The results obtained in this work proved the potential of Raman spectroscopy for the characterization of industrial pharmaceutical products, which was already demonstrated by several authors 20–27…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results obtained in this work proved the potential of Raman spectroscopy for the characterization of industrial pharmaceutical products, which was already demonstrated by several authors 20–27…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, because it is possible to obtain high‐quality spectra of the sample without removing it from the package, this technique enables nondestructive and noninvasive on‐line quality‐control checks to be performed on the final industrial products 20–22…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Raman spectrometers can be con gured to allow for the analysis of explosive materials in glass or plastic containers. 16 However, Lewis et al 13 noted that certain explosives (e.g., Semtex, C4, HNBP, and picric acid) exhibit uorescence even with 785-nm excitation. The impurities, rather than the sample itself, are frequently the cause of the uorescence in explosives.…”
Section: Introductionmentioning
confidence: 99%
“…8 Nevertheless, the reported applications of Raman spectroscopy to the identi cation of form ulated and packaged drug products have been minimal. 9,10 Some efforts have already been made for the application of Raman spectroscopy to the quantitative determination of active ingredients or impurities in solid dosage form s and the purity determination of bulk pharm aceutics. 9,[11][12][13][14] The main reasons for the limited quantitative applications are the sm all content of active drug in many formulated products in com bination with the small scattering cross-sections and the uorescence interference from the active substance or the excipients.…”
Section: Introductionmentioning
confidence: 99%
“…8 As a result, FT-Raman spectroscopy has been shown to be capable for the identi cation of formulated products inside plastic blister packages with minimal or no interference from the packaging material. 10,15 The capability of quantitative analysis without rem oving tablets from their PVC blister package renders FT-R aman spectroscopy a promising technique for analysis of solid pharm aceutical dosage forms.…”
Section: Introductionmentioning
confidence: 99%